Mexico : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper shows that upgrading basic public infrastructure, and road infrastructure, raises productivity among firms, not only for large companies but also for Mexico's large number of small and micro firms. This finding suggests that greater government spending on road infrastructure will support efforts to raise productivity and growth over the medium term. Mexico's infrastructure quality has been on a steady decline. World Economic Forum indicators of perceived infrastructure quality show Mexico broadly in line with-or even outperforming-its emerging market and regional peers. Infrastructure quality and access are likely to weaken further at current investment rates. Spending trends compare particularly poorly to investment needs in the case of roads investment. According to the Global Competitiveness Index, the perceived quality of Mexico's transportation infrastructure is broadly in line with peers. The note provides evidence of the role of infrastructure investment in boosting productivity.